Macroglobulinemia: hidden by anemia (clinical case report) - Svetlana M. Khokhlova; Olga N. Pasyuta; Julia B. Chervyakova; Margarita A. Gromova; Julia G. Patraman; Alexander A. Kopelev; Tamara O. Myshlyaeva (LLC "MEDIAFORMAT", 2023)
Waldenström macroglobulinemia (WM) is a type of plasma cell disease that is a malignant B-cell lymphoplasmacytic lymphoma. In patients with WM, immunological blood tests may remain unchanged for a while without pathological changes, but then tumor infiltration of the bone marrow gradually leads to anemia and thrombocytopenia. This patient has anemic syndrome according to clinical and laboratory examination, in which a number of diseases were diagnosed. An early diagnostic method, electrophoresis allows the consideration of immunoproliferative disorders with monoclonal IgM. Immunotyping is widely used with the eye chart of gammopathies using antisera to light (G, A, M) and light (kappa, lambda) chains of immunoglobulins. An increase in blood vessels IgM > 30 g/l, when identified with neurological symptoms of the source, associate these manifestations with hyperviscosity syndrome in WM.